Tetrahedral Imidazolate Frameworks with Auxiliary Ligands (TIF-Ax): Synthetic Strategies and Applications - Tong Hao; Hui-Zi Li; Fei Wang; Jian Zhang (Molecules, 2023)
Zeolitic imidazolate frameworks (ZIFs) are an important subclass of metal–organic frameworks (MOFs). Recently, we reported a new kind of MOF, namely tetrahedral imidazolate frameworks with auxiliary ligands (TIF-Ax), by adding linear ligands (Hint) into the zinc–imidazolate system. Introducing linear ligands into the M2+-imidazolate system overcomes the limitation of imidazole derivatives. Thanks to the synergistic effect of two different types of ligands, a series of new TIF-Ax with interesting topologies and a special pore environment has been reported, and they have attracted extensive attention in gas adsorption, separation, catalysis, heavy metal ion capture, and so on. In this review, we give a comprehensive overview of TIF-Ax, including their synthesis methods, structural diversity, and multi-field applications. Finally, we also discuss the challenges and perspectives of the rational design and syntheses of new TIF-Ax from the aspects of their composition, solvent, and template. This review provides deep insight into TIF-Ax and a reference for scholars with backgrounds of porous materials, gas separation, and catalysis.